Determinasi Kejadian Perilaku Seksual Pranikah dalam Aktivitas Pacaran Remaja di Kalimantan Tengah - Shesanthi Citrariana; Risqika Yuliatantri Paramawidhita; Halida Suryadini; Muhammad Dawam; Awumistiko Awumistiko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Based on the 2017 IDHS survey, most adolescent women (80%) and men (84%) reported dating. The 15-17 years is the age group when adolescents start dating. Teenage dating activities lead to sexual behavior, such as holding hands, hugging, kissing lips, touching sensitive parts, and having sex. This study aims to determine the influence of the background characteristics of adolescents (age, area of residence, level of education) and social patterns (having friends having premarital sex, having the urge because of friends, influencing friends to have premarital sex, considering virginity important) on the incidence of premarital sex in Central Kalimantan 2017. Secondary data were obtained from the 2017 IDHS survey. Data analysis was performed by univariate, bivariate (Spearman rho test), and multivariate (logistic regression test). The results showed that 88% of respondents had sexual behavior orientation, and 12% did not. The correlation analysis explains a significant relationship between premarital sexual behavior and the area of residence. Respondents who live in cities are 3.47 times more likely to commit premarital sexual behavior (α<0,05 = 0,021; OR = 3.47). In addition, there is sufficient evidence to suggest a relationship between premarital sexual behavior and education level, respondents who attend high school and above are 2.71 times more likely to have premarital sexual behavior (α<0,10 = 0,066; OR = 2.71). Meanwhile, other variables from background characteristics and social patterns have no significant relationship/do not influence premarital sexual behavior. So it can be concluded that the background characteristics in the area of residence (Sig Wald <0.0) have a significant partial effect on adolescents' incidence of premarital sexual behavior in Central Kalimantan.